2021
DOI: 10.3390/brainsci11070900
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Task-Induced Neurological Outcome after Stroke

Abstract: Electroencephalography (EEG) can access ischemic stroke-derived cortical impairment and is believed to be a prospective predictive method for acute stroke prognostics, neurological outcome, and post-stroke rehabilitation management. This study aims to quantify EEG features to understand task-induced neurological declines due to stroke and evaluate the biomarkers to distinguish the ischemic stroke group and the healthy adult group. We investigated forty-eight stroke patients (average age 72.2 years, 62% male) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 35 publications
0
72
0
Order By: Relevance
“…The area under the ROC curve (AUC) for the IAR, IVR, and NR models were 0.979, 0.976, and 0.957, respectively. While these additional metrics are provided in keeping with the conventions of other machine learning studies in the field of stroke medicine [16,18,19,22,23,38], it should be noted that their interpretation is complicated by the fact that voxel-based tissue outcome prediction is a highly imbalanced problem. That is to say, the vast majority of brain tissue voxels will not proceed to infarction and are easy to identify as such, leading to especially high values for accuracy, specificity, and the area under the ROC curve (AUC), which may not intuitively reflect the ability of the model to discriminate between healthy and ischemic voxels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The area under the ROC curve (AUC) for the IAR, IVR, and NR models were 0.979, 0.976, and 0.957, respectively. While these additional metrics are provided in keeping with the conventions of other machine learning studies in the field of stroke medicine [16,18,19,22,23,38], it should be noted that their interpretation is complicated by the fact that voxel-based tissue outcome prediction is a highly imbalanced problem. That is to say, the vast majority of brain tissue voxels will not proceed to infarction and are easy to identify as such, leading to especially high values for accuracy, specificity, and the area under the ROC curve (AUC), which may not intuitively reflect the ability of the model to discriminate between healthy and ischemic voxels.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that this correlation also holds true for follow-up lesions predicted from acute PWI data [49], raising the possibility that mRS scores could be predicted directly from acute image data and clinical information in future and used in the same manner as the prediction lesion volume for an in silico evaluation. As mRS is used as both a clinical and a functional outcome, an imaging-based approach to predicting mRS would likely benefit from the availability of information about the infarct location, which adds valuable context when interpreting the functional severity of stroke from the lesion volume [50], as well as the potential to add salient covariates [51] and additional neurological data [38] to the model. More recently, it has been suggested that the post-treatment NIHSS score may be a suitable alternative primary outcome measure to mRS for clinical trials of acute ischemic stroke [52].…”
Section: Discussionmentioning
confidence: 99%
“…Each block started with a 10 s baseline. The power of the delta [1-4 Hz], theta [4][5][6][7][8], alpha [8][9][10][11][12][13][14], beta [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and gamma [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] band were used to compare both systems in the frequency domain. Moreover, the topographical distribution of the alpha band was used to compare both systems in the spatial domain.…”
Section: Eyes Open/eyes Closed Task (Eoec)mentioning
confidence: 99%
“…Electroencephalography (EEG) is an electrophysiological measurement technique that records the electrical activity of the cerebral cortex with a high temporal resolution, using non-invasive scalp electrodes [1]. In research, it is a widely used technique to investigate visual, auditory, and cognitive functioning, as well as to gain insights, for instance, into the cortical pathways and impairments involved in neurological (movement) disorders [2], such as Parkinson's disease [3] or stroke [4]. More recently, EEG has become an important tool in research on brain-computer interfaces [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Functional motor and cognitive deficits are usual and persistent consequences of stroke and a significant factor responsible for physical dysfunction, slow physiological recovery, and a worse post-stroke lifestyle [ 10 ]. Conventional mental and neurological evaluations cannot be conducted immediately after stroke due to the medical aspects (e.g., fluctuating levels of arousal, pain, confusion, tiredness) and functional obstacles (e.g., sensory, linguistic, motor shortfalls) that hamper the patients’ capability to approach physiological examinations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%